Integration of Ethylene and Light Signaling Affects Hypocotyl Growth in Arabidopsis - Yu, Yanwen; Huang, Rongfeng (Frontiers in Plant Science, 2017)
As an ideal model for studying ethylene effects on cell elongation, Arabidopsis hypocotyl growth is widely used due to the unique characteristic that ethylene stimulates hypocotyl elongation in the light but inhibits it in the dark. Although the contrasting effect of ethylene on hypocotyl growth has long been known, the molecular basis of this effect has only gradually been identified in recent years. In the light, ethylene promotes the expression of PHYTOCHROME INTERACTING FACTOR 3 (PIF3) and the degradation of ELONGATED HYPOCOTYL 5 (HY5) protein, thus stimulating hypocotyl growth. In the dark, ETHYLENE RESPONSE FACTOR 1 (ERF1) and WAVE-DAMPENED 5 (WDL5) induced by ethylene are responsible for its inhibitory effect on hypocotyl elongation. Moreover, CONSTITUTIVE PHOTOMORPHOGENIC 1 (COP1) and PHYTOCHROME B (phyB) mediate the light-suppressed ethylene response in different ways. Here, we review several pivotal advances associated with ethylene-regulated hypocotyl elongation, focusing on the integration of ethylene and light signaling during seedling emergence from the soil.